PENGARUH CORPORATE IMAGE INDEX TERHADAP CITRA PERUSAHAAN PELABUHAN INDONESIA I - Hashim Thaci; Dedi Kurnia Syah (Jurnal Ranah Komunikasi, 2021)
The purpose of this research are: (1) the influence of corporate image index on corporate image Pelindo I, (2) calculate the number of influence corporate image index on corporate image Pelindo I. Sample in this research using purposive with explanatory research method. The instrument which are used in this research were corporate image index instrument consists of 20 question and the instrument of corporate image consists of 16 question that were declared valid and reliable. The result of this research are: (1) there were a causal effect between corporate image index on corporate image PT. Pelabuhan Indonesia I, (2) the number of causal effect of corporate image index on corporate image is 74,4%.